Political Science in The Age of Resentment - D. B. Kazarinova (Vestnik MGIMO-Universiteta)
Review of the book «Modern political science: Methodology» ed. by O. V. Gaman-Golutvina and A. I. Nikitin, Moscow, Aspect Press, 2019.The article examines some of the resentment related issues of modern politics, using a number of methodological approaches (identitarian approach, constructivist institutionalism, cultural and civilizational approaches, psychological-political and elitist, as well as gender approaches), described in the collective work of the Russian renowned academics "Modern political science: Methodology". These are the cleavages between traditional politics vs post- and pseudo-politics (shift from the normal politics made by consolidating broad strata to self-centered, exclusive, and increasingly differentiated and closed groups of pseudo-policies), conventional political leadership vs populism and anti-elitism (the rapid growth of populists on a global scale, the spread of anti-establishment sentiment, "populism of power" and the crisis of responsible leadership), formal and informal institutions vs personification of politics (reducing the role of institutions and increasing the importance of the human factor ), socio-economic basis of policy vs socio-cultural basis (emphasis on ethnic, religious and gender factors). The resentment as both the cause and effect of identity politics, is a result of an unfair distribution of goods and evils of globalization, or the manifestation of accumulated negative emotions and unjustified expectations. It generalizes these trends and issues and requires new research approaches, since traditional rationalistic approaches based on the theory of rational choice become less effective. To meet the challenges of resentment era, political science should keep balance between rationalism and reflexivity. This balance provides a single epistemological basis for the study of current political reality. It has been successfully reached by the authors of the book "Modern political science: Methodology". The book posits the idea of the fundamental irreducibility of methodology to the sum of the methods. In this regard the volume differs from similar publications aiming to present a wide scope of political methodology. The logic of the representation used by the editors is moving from general to particular, from societal to human, from global to local. The book demonstrates the wide diversity of methodological approaches and the rejection of the ideas of universalism, which adequately characterizes the state of Russian political science. The work is remarkable because it not only reflects, but also structures the Russian political science.